2017
DOI: 10.1007/s12011-017-1036-9
|View full text |Cite
|
Sign up to set email alerts
|

Pectin Esterification Degree in the Bioavailability of Non-heme Iron in Women

Abstract: Pectins are a type of soluble fiber present in natural and processed foods. Evidence regarding the effect of esterification degree of pectins on iron absorption in humans is scarce. In the present study, the effect of pectins with different degrees of esterification on non-heme iron absorption in women was evaluated. A controlled experimental study was conducted with block design, involving 13 apparently healthy, adult women. Each subject received 5 mg Fe (FeSO) without pectin (control) or accompanied by 5 g c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Jaramillo et al, assessed the effect of 5 g of pectin with various degrees of esterification on iron absorption with 5 mg of FeSO 4 in healthy women. There were no significant differences depending on the degree of pectin esterification [ 53 ]. In another study, the same author showed no effect of pectin in a dose of 250 mg on the bioavailability of iron with FeSO 4 in the fasting women [ 54 ].…”
Section: Prebiotics In Anemiamentioning
confidence: 99%
“…Jaramillo et al, assessed the effect of 5 g of pectin with various degrees of esterification on iron absorption with 5 mg of FeSO 4 in healthy women. There were no significant differences depending on the degree of pectin esterification [ 53 ]. In another study, the same author showed no effect of pectin in a dose of 250 mg on the bioavailability of iron with FeSO 4 in the fasting women [ 54 ].…”
Section: Prebiotics In Anemiamentioning
confidence: 99%